2015
DOI: 10.7718/ijec.v15i1.1000
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Potential Sources of Heavy Metals in Major Irrigated Rice Areas of the Philippines

Abstract: Industrialization, urbanization and intensive use of farm inputs can pollute agricultural areas. The study was then conducted to assess the levels of chromium (Cr), nickel (Ni), copper (Cu), cobalt (Co), zinc (Zn), arsenic (As), molybdenum (Mo), cadmium (Cd), mercury (Hg), and lead (Pb) in the country’s major rice areas. The study also determined the contributions of soil properties, land uses, irrigation water, and farm inputs to the metal levels. Strategic collections of soil, plant and water samples in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Zn-deficient paddy soils were identified for rice plants based on the results of the Minus-One Element Technique (MOET) followed by Descalsota et al (137). A significant positive correlation and linear regression between soil Zn and plant Zn were observed by Magahud et al (25), indicating that higher soil concentrations of Zn lead to higher Zn concentration in rice plants. The concentration of Zn in rice, particularly in the grains, is highly affected by the amount of bioavailable Zn in the soil (117, 130).…”
Section: Co-location Of Zn Deficiencies In Philippine Soils and Populmentioning
confidence: 79%
See 2 more Smart Citations
“…Zn-deficient paddy soils were identified for rice plants based on the results of the Minus-One Element Technique (MOET) followed by Descalsota et al (137). A significant positive correlation and linear regression between soil Zn and plant Zn were observed by Magahud et al (25), indicating that higher soil concentrations of Zn lead to higher Zn concentration in rice plants. The concentration of Zn in rice, particularly in the grains, is highly affected by the amount of bioavailable Zn in the soil (117, 130).…”
Section: Co-location Of Zn Deficiencies In Philippine Soils and Populmentioning
confidence: 79%
“…In another study conducted by Magahud et al (25), which assessed the levels of heavy metals, including Zn, in the country's major rice production areas found that Zn concentrations are generally low in rice production areas. Figure 2 presents the results of the studies on the concentrations of micronutrients, particularly Fe and Zn.…”
Section: Iron and Zinc Status Of Philippine Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to land degradation and affects the agricultural land use. This condition was also discussed in the work of Barman et al (2000); Intangwogse and Dean (2007); Kumar, (2013); Magahud et al (2015); Marquez et al (2018). These works were carried out 'in-vitro', applied research in Philippines (specifically in Zambales and Negros Occidental) and Vietnam, respectively.…”
Section: Heavy Metals In Some Agricultural Yieldsmentioning
confidence: 96%
“…The majority of stream sediment samples (N = 39) collected from the Zambales Mountain Range in Central Luzon contained 0.05-1.0 ppm As, while the highest measured was 114.8 ppm [8]. A study on rice paddy soil samples revealed As values beyond the soil background value of 9.0 ppm in some parts of Laguna (15.5 ppm) and Camarines Sur (9.2 ppm) in Luzon and Negros Occidental (11.4 ppm) in Visayas [9]. Groundwater samples from Central Luzon were found to contain As beyond the 2017 Philippine National Standards for Drinking Water (PNSDW) limit of 10 ppb, with values as high as 300 ppb [7].…”
Section: Introductionmentioning
confidence: 95%